Impact of Surface Chemistry on the Removal of Indigo Carmine Dye Using Apricot Stone Active Carbon - Hamdi M.H. Gad; Abd. El-Hakim; A.M. Daifullah (Adsorption Science & Technology)
A biomass agricultural waste material, i.e. apricot stone, was used as an adsorbent either as received (AP), after carbonization at 500°C (C-AP), and after chemical activation using H 3 PO 4 (H-APC) or using KOH (K-APC) followed by carbonization at 500°C. The four adsorbents were characterized by various techniques (e.g. BET specific surface area measurements, FT-IR spectroscopy and measurements of the total pore volume, density, pH and moisture content). Preliminary investigations showed that the highest uptake was exhibited by K-APC. Factors affecting the removal of Indigo Carmine (IC) dye using K-APC were investigated. The amounts of co-existing ions as well as those removed during the desorption process were determined quantitatively. The results obtained were examined using two-parameter equilibrium models (Langmuir and Freundlich equations). Studies of the process at 30, 50 and 70°C demonstrated that adsorption was endothermic. The effects of cations, e.g. K + , Na + , Ca 2+ , Mg 2+ and Al 3+ , on dye removal were investigated. The monolayer capacity of K-APC was 552.5 mg/g. The proposed mechanism suggests that surface chemistry rather than the surface texture of the activated carbon plays a significant role in the process. Thus, K-APC can be considered as a novel adsorbent for the removal of IC dye from waste effluents.